2009
DOI: 10.1007/s11605-008-0756-8
|View full text |Cite
|
Sign up to set email alerts
|

Is Gum Chewing Useful for Ileus After Elective Colorectal Surgery? A Systematic Review and Meta-Analysis of Randomized Clinical Trials

Abstract: In patients with ileus after colonic surgery, gum chewing in addition to standard treatment significantly reduces the time to first flatus and the time to first passage of feces when compared to standard treatment alone. There is also a trend to reduce the length of hospital stay. Gum chewing should be added to the standard treatment of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 34 publications
2
46
1
2
Order By: Relevance
“…As noted above, the appropriate use of epidurals and maintaining a near-zero fluid balance are associated with an enhanced return of bowel activity after abdominal surgery [88,146]. Chewing gum has been shown to be safe and beneficial in restoring gut activity after colorectal surgery [176][177][178] Postoperative artificial nutrition Most patients tolerate normal oral intake soon after elective PD. Early oral intake in this patient group has been shown to be feasible and safe [6,144].…”
Section: Summary and Recommendationmentioning
confidence: 99%
“…As noted above, the appropriate use of epidurals and maintaining a near-zero fluid balance are associated with an enhanced return of bowel activity after abdominal surgery [88,146]. Chewing gum has been shown to be safe and beneficial in restoring gut activity after colorectal surgery [176][177][178] Postoperative artificial nutrition Most patients tolerate normal oral intake soon after elective PD. Early oral intake in this patient group has been shown to be feasible and safe [6,144].…”
Section: Summary and Recommendationmentioning
confidence: 99%
“…The use of chewing gum has emerged as a further, new, novel and simple strategy for preventing postoperative ileus. Several studies have reported on the beneficial effect of using chewing gum after surgery to limit the incidence of ileus [6][7][8] . This study aimed to determine whether gum chewing in the immediate postoperative period facilitates a return to bowel function after cesarean section.…”
Section: Influence Of Gum Chewing On Postoperative Bowel Activitymentioning
confidence: 99%
“…No limitation based on language and publication status Three meta-analyses 15,16,18 limited the publication language to English. The remaining two meta-analyses 19,22 restricted the written language to English and Chinese.…”
Section: Search Methodologymentioning
confidence: 99%